2009
DOI: 10.12693/aphyspola.115.363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Deposition Temperature οn Magnetotransport Properties οf Ni-Fe/Au/Co/Au Multilayers

Abstract: A correlation between the growth process and electrical properties of [Ni80Fe20(2 nm)/ Au(2 nm)/Co(0.8 nm)/Au(2 nm)]15 multilayers is presented. A set of multilayers of identical composition was deposited in different temperatures. The changes in giant magnetoresistance amplitude were correlated with the changes in Co layers growth process that occur in different temperatures. The in situ conductance measurement leads to the growth mechanism identification in high temperatures as formation of Co islands. Inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In case of the ∆p(N −1 ) dependence for Au/Co interfaces in Mls deposited at T D = 150 • C, the grain boundary scattering exceeds the sublayer boundary scattering in the entire range of N , causing almost zero values of ∆p for each N . It correlates with enhanced Volmer-Weber growth mode of Co at Au surface [8,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of the ∆p(N −1 ) dependence for Au/Co interfaces in Mls deposited at T D = 150 • C, the grain boundary scattering exceeds the sublayer boundary scattering in the entire range of N , causing almost zero values of ∆p for each N . It correlates with enhanced Volmer-Weber growth mode of Co at Au surface [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the changes in magnetotransport properties of [Py(2 nm)/Au(2 nm)/Co(0.8 nm)/Au(2 nm)] 15 Mls induced by deposition temperatures variations were reported [8,9]. It was found that application of deposition temperature T D > 25 • C enhances the three--dimensional growth of Co at Au surfaces, which leads to the discontinuous character of Co sublayers deposited at T D = 150 • C. Co islands in (Py/Au/Co/Au) 15 systems were found to be superparamagnetic in nature [9].…”
Section: Introductionmentioning
confidence: 99%